Serum Homocysteine and Methionine as Complementary Biomarkers in the Early Detection of Myocardial Infarction - Ghassan Mhalhal; Helen Mohsen (American Journal of Biomedicine and Pharmacy, 2025)
This paper tries to establish a concept about the role of homocysteine and methionine in early diagnosis of patients with myocardial infraction. this research aims to make a comparison between the concentration of homocysteine and methionine along with lipids spectrum. A case control study required 80 of recruitments (40 diagnosed with myocardial infraction as patients and 40 healthy people as control group). Homocysteine and methionine concentration were assessed by high performance liquid chromatography (HPLC) and lipid profile parameters were measured by Cobas C 111 analyzer. According to the result taken has found that myocardial infraction patients show highly significant amount of homocysteine, cholesterol, triglyceride and LDL, but low values of methionine and HDL values when compared to control group. In hence homocysteine could be present as a strong diagnostic biomarker to early diagnose MI cases, moreover these findings are just altered amino acid and lipid metabolism in patients with myocardial infraction. the integration of these biomarkers in specific homocysteine could be a suitable diagnostic marker and may improve early detections of MI. furthermore the ways of understanding the mechanism of methionine role in methylation pathway could open a new avenue for therapeutic intervention targeting metabolic and vascular health and high-risk individuals.